One-piece Orbitozygomatic Craniotomy for Resection of Rathke's Cleft Cyst: Operative Video - Dossani, Rimal H. (J Neurol Surg B Skull Base, 2018)
Objective  The video stars orbitozygomatic resection of Rathke's cleft cyst with suprasellar extension in a 37-year-old male patient presenting with severe headaches and bitemporal hemianopia. Clinical and radiological characteristics along with surgical technique (positioning, bony opening, surgical dissection and debulking, closure), histopathology, and postoperative course are described. Methods  Preoperative MRI demonstrated a noncontrast-enhancing cystic lesion in the sella with suprasellar extension causing compression of both optic nerves. A one-piece orbitozygomatic craniotomy was performed. The tumor was encountered in the interoptic space. First, the cyst was decompressed and fluid appearing like motor oil was aspirated. Both optic nerves were decompressed and dissected free from the cyst wall. Intraoperatively, the most challenging aspect was separating the tumor from surrounding vascular structures, including bilateral A1 arteries and the left carotid bifurcation. A combination of sharp and blunt dissection was utilized to free the tumor from adhesions to critical neurovascular structures. Once freed, the suprasellar aspect of the tumor was mobilized into the operative cavity and debulked. Finally, the sellar component of the tumor was removed all the way down to the sellar floor. Postoperative MRI demonstrated decompressed bilateral optic nerves with an intact pituitary stalk with preservation of normal pituitary gland. Histopathology identified pathognomonic features consistent with diagnosis of Rathke's cleft cyst, including flattened ciliated epithelium and presence of Rathke's cleft remnants. Results  Postoperatively, bilateral improvement in vision was noted with transient diabetes insipidus. Patient was discharged home on postoperative day 4. Conclusion  A one-piece orbitozygomatic craniotomy is an effective and safe strategy for resection of Rathke's cleft cysts with suprasellar extension. The link to the video can be found at: https://youtu.be/-Yqtcd2gLSs .